The Effect of Polyurethane Film Versus Apis Dorsata Honey Spray for Wound Dressing Following Long Bone Fractures Osteosynthesis - Surianty Shafei; Mohd Ariff Sharifudin; Shaifuzain Ab Rahman; Abdul Nawfar Sadagatullah (Gazi Medical Journal)
Objective: Surgical site infection (SSI) following implant-related fracture osteosynthesis remains a burden and challenging for orthopedic surgeons. Honey-based dressings can be used as prophylactic agents. Methods: This prospective, randomized clinical study was designed to compare the effect of conventional polyurethane film and Apis dorsata honey spray as dressing materials after long bone fracture osteosynthesis. Results: Forty participants with closed tibial or femoral diaphyseal fracture treated with open reduction and internal osteosynthesis with intramedullary implants or plates and screws were randomly divided into 3 groups: 16 were dressed with polyurethane film (group A), 13 with Apis dorsata honey spray (group B), and 11 as controls. Wounds of the two groups were dressed using a similar wound protocol immediately (D0) and three days (D3) after surgery. In the control group, wounds were treated with non-adhesive film only. All wounds were evaluated on day 14 (D14) and day 42 (D42) for local complications and the effects on skin commensals. On D42, wound dehiscence and scar formation were also evaluated. Acinobacter species were isolated from a control. Conclusion: One patient from group A had superficial SSI. There was no significant association between wound healing and the dressing materials used. Honey dressing reduced the risk of hypertrophic scar formation. Other outcomes were comparable between groups A and B. Apis dorsata honey is a safe alternative dressing that is comparable to polyurethane film as a dressing material following long bone fracture osteosynthesis.